FACTORS AFFECTING ACCOUNTING LEARNING ACHIEVEMENT AMONG UNIVERSITY STUDENTS - Vina Ariany; Amir Indra Budiman (STMIK Indonesia Banda Aceh, 2026)
This study aims to examine the effect of emotional intelligence, campus environment, learning style, learning discipline, and learning motivation on students’ accounting learning achievement at Universitas Budi Luhur Jakarta. This research uses a quantitative approach with a survey method involving 100 accounting students selected through purposive sampling. Data were collected using questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that emotional intelligence, campus environment, learning style, learning discipline, and learning motivation have a positive and significant effect on accounting learning achievement. These findings indicate that behavioral and environmental factors play an important role in improving students’ academic performance. Therefore, universities are expected to develop learning strategies and academic policies that support students’ behavioral aspects and create a conducive learning environment.